INTERPRETASI BAWAH PERMUKAAN MENGGUNAKAN METODE GPR (GROUND PENETRATING RADAR) DI AMBLESAN JALAN RING ROAD II KOTA SAMARINDA - Putro, Ari Anggono; Supriyanto, Supriyanto; Rinaldi, Aditya (Geophysics Study Program, Faculty of Mathematics and Natural Sciences, Mulawarman University, 2019)
This research has been conducted using the Ground Penetrating Radar method to interpretation subsurface conditions that have the potential to become Subsidence on Jalan Ring Road II Samarinda. East Kalimantan, Ground Penetrating Radar Method is a geophysical method that utilizes the propagation of electromagnetic waves to identify subsurface structures, where the recorded penetration of depth and amplitude is affected by the dielectric properties of a material. This study uses an antenna with a frequency of 100 MHz. Based on the interpretation of radar data the potential for a subsidence to occur on track 1 and track 2, in this layer explains that there is a weak field that occurs due to infiltration where the entry of water flow into the soil through the surface of the ground and the condition of the road is steep so that water easily enters the area that has experienced subsidence due to fractures. On lines 3 and 4 there are several different amplitude intervals that are marked by changes in color on radar data which results in factors of material heterogeneity or water content in the layer.